The Government's Practices in The Strategy for the Development of the State's Businesses - Fika Nurtivanny; Imsar Imsar; Aqwa Naser Daulay (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This research aims to determine alternative government policies for developing songket weaving business strategies in Batu Bara Regency. The SOAR approach is the technique that the author employs to analyze this research. (Strengths, Opportunities, Aspirations, and Results) with a descriptive approach where, when gathering information from interviewees. In light of the analysis of internal factors of Songket Weaving Crafts obtained the IFA matrix's calculated findings, which show a score of 3.425. Meanwhile, the result on the discoveries of the examination of the songket weaving craft's internal environment, the EFA matrix calculation results were obtained with a score of 2.31. Based on the SOAR matrix, there are two important elements in the business development strategy obtained from O-A, namely: increasing business development by expanding marketing by taking advantage of export opportunities; improving the economy through songket crafts in Batu Bara Regency with the high public interest in songket cloth. The development of the songket weaving business really requires government support and a role to improve the creative economy in Batu Bara Regency.